2022
DOI: 10.1080/21681805.2022.2030401
|View full text |Cite
|
Sign up to set email alerts
|

The transferability of the minimal invasive surgeon’s skills to open surgery

Abstract: Background: Robot-assisted laparoscopic surgery has gained popularity, which has contributed to a decrease in the number of open procedures. Hence a growing concern regarding the ability of laparoscopically trained surgeons to perform open surgery (e.g. due to bleeding complications) has been raised. The aim of the study was to investigate the ability of conversion to open surgery following exclusively robotic or laparoscopic training. Methods: Thirty-six medical students were randomized into three groups: Ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Study participants were randomly assigned to one of three groups: laparoscopic, open surgery, or robotic training. The training setup has previously been described [ 12 ]. In summary, they were given a baseline evaluation (pre-training test) in the surgical modality to which they were assigned.…”
Section: Methodsmentioning
confidence: 99%
“…Study participants were randomly assigned to one of three groups: laparoscopic, open surgery, or robotic training. The training setup has previously been described [ 12 ]. In summary, they were given a baseline evaluation (pre-training test) in the surgical modality to which they were assigned.…”
Section: Methodsmentioning
confidence: 99%
“…Surgical techniques in medicine are subject to ongoing development 1 . Especially in the era of minimally invasive and robotic-assisted surgery, surgeons are constantly exposed to new techniques and surgical procedures, which signify new training options 2 and require a high level of skill in terms of adaptation and learning.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Investigators have also examined the use of simulators specifically created for training in robotic surgery for training in other surgical modalities, such as laparoscopic and open surgery. 14,15 The major difference between robotic simulators and laparoscopic box simulators utilizing straight instruments are the 3-D field of view and enhanced dexterity in instrumentation, with improved degrees of freedom and articulation as well as improved ergonomics for the participant that are provided by the robotic simulators. 16 Studies 14,17,18 have shown that objective improvement in scores on validated 3-D simulators correlated with improved live surgical procedure outcomes.…”
mentioning
confidence: 99%
“…14,15 The major difference between robotic simulators and laparoscopic box simulators utilizing straight instruments are the 3-D field of view and enhanced dexterity in instrumentation, with improved degrees of freedom and articulation as well as improved ergonomics for the participant that are provided by the robotic simulators. 16 Studies 14,17,18 have shown that objective improvement in scores on validated 3-D simulators correlated with improved live surgical procedure outcomes. Robotic simulators have even been used for open surgical training because the psychomotor skills acquired are similar to traditional open surgical skills.…”
mentioning
confidence: 99%
See 1 more Smart Citation